2015
DOI: 10.3889/oamjms.2015.065
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Copper, Ceruloplasmin and Angiotensin Converting Enzyme among Silicotic and Non-Silicotic Workers

Abstract: BACKGROUND:Silicosis is the most frequently occurring pneumoconiosis.AIM:Measurement of serum levels of Angiotensin converting enzyme (ACE), Copper (Cu) and Ceruloplasmin (Cp) in cement workers occupationally exposed to silica dust as biomarkers of exposure rather than biomarkers of effect for silicosis.METHODS:Plain chest X-ray & pulmonary functions were done for 30 silicotic and 42 non-silicotic workers and 42 controls. CT scan was done for the exposed groups. Serum levels of Cu, Cp and ACE were estimated.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…Therefore, we measured these peptides of the RAS in silicotic patients and compared them with those in non‐silicotic workers. Unfortunately, our findings were not in agreement with other studies (Beshir, Aziz, Shaheen, & Eltahlawy, ; Zielonka et al., ); we only found an increase in ACE in patients with silicosis phase III and an upregulation of Ang II in silicosis phase I. Furthermore, we also found that Ang‐(1–7) was elevated in silicosis phase II and Ac‐SDKP was increased in silicosis phase III compared with non‐silicotic patients.…”
Section: Discussioncontrasting
confidence: 98%
“…Therefore, we measured these peptides of the RAS in silicotic patients and compared them with those in non‐silicotic workers. Unfortunately, our findings were not in agreement with other studies (Beshir, Aziz, Shaheen, & Eltahlawy, ; Zielonka et al., ); we only found an increase in ACE in patients with silicosis phase III and an upregulation of Ang II in silicosis phase I. Furthermore, we also found that Ang‐(1–7) was elevated in silicosis phase II and Ac‐SDKP was increased in silicosis phase III compared with non‐silicotic patients.…”
Section: Discussioncontrasting
confidence: 98%
“…This situation was in reversed tendency after treatment with arctiin and arctigenin (Figures S2a-S2f). Serum lysozyme and ceruloplasmin were increased in dust-induced PF [30,31] because lysosomes in cells were damaged and released lysozymes to stimulate fibroblast proliferation after macrophages swallowed the dust [32]. Ceruloplasmin promoted amino oxidation of lysine in peptide chains and eventually resulted in the formation of collagen fibrosis [33].…”
Section: Resultsmentioning
confidence: 99%
“…1B). Similarly, several previous studies have reported that increased circulating levels of copper associate with fibrosis and organ damage (liver, lung, oral submucous tissue) in animals [3][4][5] and humans 18,19 ; however, the mechanism by which an elevated serum copper concentration leading to intracellular copper overload could induce organ fibrosis was not investigated in these studies.…”
Section: Discussionmentioning
confidence: 97%